Dual-purpose high-efficiency air filter paper loaded with reactive zirconium hydroxide for the filtration aerosols and degradation of chemical warfare agents. Issue 56 (1st November 2021) - Huang, Xingqi; Zhao, Ting; Zhang, Hongpeng; Yan, Chunxiao; Sha, Jiulong; Tang, Huamin; Zhu, Haiyan; Wu, Yue
Abstract : Dual-functional air filter paper with addition of Zr(OH)4 was prepared by an intra-pulp addition method, whose filtration performance is maintained while the decontamination performance is added for HD and VX. Abstract : Traditional air filter papers can only filter toxic aerosols without the function of decontamination. If the poison stagnating in the paper is desorbed, it may pose a secondary threat to personnel and make it more difficult to dispose of the scrapped paper. Using an alkali-free glass fiber as the base material and zirconium hydroxide as the decontaminant, a self-decontaminating air filter paper that can degrade HD and VX simultaneously was successfully prepared by an intra-pulp addition method, with high filtration efficiency, low pressure drop and moderate tensile strength. The physicochemical properties were characterized by FE-SEM, EDX, XRD and TGA, and the results indicated that Zr(OH)4 was dispersed uniformly in the paper and filled in the interstices of the glass fiber. The preparation of the composite material had no impact on the structure of fibers and Zr(OH)4 . The preparation technology of the self-decontaminating air filter paper was optimized. It was found that the paper with a fiber grammage of 50 g m −2, the adhesive of 2% and a Zr(OH)4 retention rate of 175.0 wt% could completely degrade HD and VX, whose conversion rate exceeded 99.0%, and had a tensile strength of 0.1193 kN m −1, a filtration efficiency of 99.995%, and a pressure drop of 313.6 Pa. Using GC-MS to detect the decontamination products, it was speculated that HD mainly underwent hydrolysis and elimination reactions, VX mainly underwent hydrolysis and polymerization reactions, and their products were non-toxic or low-toxic. The reaction kinetics of HD and VX on the paper was investigated and the half-lives were 2.6 h and 16.2 min, respectively, which demonstrated an outstanding degradation performance. This work manifested for the first time that the air filter paper can be optimized as an efficient self-decontaminating material, which will open up new possibilities for the design and manufacture of multifunctional protective materials.